The Guided Inquiry Model of Scientific Literacy: A Meta-Analytic Study - Farhan, Muhammad; Saregar, Antomi; Yuberti, Yuberti (UIN Fatmawati Sukarno Bengkulu, 2023)
In the last ten years, there have been many studies on learning models that can increase scientific literacy. One of the models studied is the Guided Inquiry learning model with varying results. So this study aims to verify how much influence the Guided Inquiry model has on students' scientific literacy based on category, level of education, and based on time zones in the territory of Indonesia. This study uses a quantitative descriptive method. Data collection was taken from the last ten years (2013-2022), which was carried out in the Scopus database, Google Scholar, and ERIC (Education Resources Information Center). The number of articles that became the population in this study was 111 articles and 20 articles as samples that met the criteria of this study. The result of the Effect Size on the Guided Inquiry model on scientific literacy is 2.65 in the high category. The effect size of the Guided Inquiry model on scientific literacy based on education level from Elementary School (SD) is 2.29, at the Junior High School (SMP) level is 2.44, at the Senior High School (SMA) level is 3.13, and at university level of 1.45. Effect Size of the Guided Inquiry model on scientific literacy based on the time zone in Indonesia. In the Western Indonesian time zone, it is 3.40 and in the Central Indonesian time zone, it is 2.103. So that the Guided Inquiry model can improve students' scientific literacy skills.